Low-profile dual mini-fragment plating of diaphyseal clavicle fractures: a biomechanical comparative testing - Pastor, Torsten; Knobe, Matthias; Wall, Bryan J. M. van de; Rompen, Ingmar F.; Zderic, Ivan; Visscher, Luke; Link, Björn-Christian; Babst, Reto; Gueorguiev, Boyko; Beeres, Frank J. P. (Clinical biomechanics, 2022)
Background - Implant removal rates after clavicle plating are high. Recently, low-profile dual mini-fragment plate constructs have revealed lower implant removal rates following fixation of diaphyseal clavicle fractures. However, they have not been subject to a biomechanical investigation. - Aims - To: (1) investigate thebiomechanical competence of different dual plate designs and (2) compare them against single superoanterior plating. - Methods - Twelve artificial clavicles with a simulated AO/OTA 15.2C unstable diaphyseal clavicle fracture were assigned to 2 groups and instrumented with dual titanium mandible plates as follows: Group 1 - 2.5 mm anterior plus 2.0 mm superior (2.5/2.0); Group 2 - 2.0 mm anterior plus 2.0 mm superior (2.0/2.0). Specimens were cyclically tested to failure under craniocaudal cantilever bending superimposed with torsion around the shaft axis and compared to previous published data acquired using 6 locking superoanterior plates tested under the same conditions (Group 3). - Findings - Initial stiffness was highest in Group 1 followed by Group 2 and Group 3, being significantly different between Group 1 and Group 3 (p = 0.020). Displacement after 5000 cycles was biggest in Group 3, followed by Group 2 and Group 1, with significant differences between Group 3 and both Group 1 and Group 2 (p ≤ 0.027). Cycles to failure were highest in Group 3 followed by Group 1 and Group 2, being significantly different between Group 2 and Group 3 (p = 0.004). - Interpretation - Low-profile 2.0/2.0 dual plates demonstrated similar initial stiffness compared with single 3.5 mm locking plates, however, they revealed significantly lower resistance to failure. Moreover, low-profile 2.5/2.0 dual plates demonstrated significantly higher initial stiffness and similar resistance to failure compared with single 3.5 mm locking plates and can therefore be considered as their useful alternative for diaphyseal clavicle fracture fixation.
Available online 28 March 2022
Gesehen am 20.06.2022